Homologous involvement of striatum and prefrontal cortex in rodent and human water maze learning. - Woolley, D; Laeremans, A; Gantois, I; Mantini, D; Vermaercke, B; Op de Beeck, H; Swinnen, S; Wenderoth, N; Arckens, L; D'Hooge, R (2013)
The multiple memory systems hypothesis posits that dorsal striatum and hippocampus are central nodes in independent memory systems, supporting response-based and place-based learning, respectively. Although our understanding of the function of hippocampus within this framework is relatively well established, the contribution of dorsal striatum is less clear. This in part seems to be due to the heterogeneous nature of dorsal striatum, which receives extensive topographically organized projections from higher cortical areas. Here we quantified neural activity in the intact brain while mice and humans acquired analogous versions of the Morris water maze. We found that dorsomedial striatum and medial prefrontal cortex support the initial acquisition of what is typically considered a hippocampus-dependent spatial learning task. We suggest that the circuit involving dorsomedial striatum and medial prefrontal cortex identified here plays a more task-independent role in early learning than currently thought. Furthermore, our results demonstrate that dorsomedial and dorsolateral striatum serve fundamentally different roles during place learning. The remarkably high degree of anatomical overlap in brain function between mouse and human observed in our study emphasizes the extent of convergence achievable with a well-matched multilevel approach.